2020
DOI: 10.1002/ece3.6811
|View full text |Cite
|
Sign up to set email alerts
|

Differences in rhizosphere microbial communities between native and non‐native Phragmites australis may depend on stand density

Abstract: Microorganisms surrounding plant roots may benefit invasive species through enhanced mutualism or decreased antagonism, when compared to surrounding native species. We surveyed the rhizosphere soil microbiome of a prominent invasive plant, Phragmites australis , and its co‐occurring native subspecies for evidence of microbial drivers of invasiveness. If the rhizosphere microbial community is important in driving plant invasions, we hypothesized that non‐native Phragmites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 36 publications
8
11
0
Order By: Relevance
“…Our experimental results are also in agreement with the only other PSF experiment on Phragmites (Allen et al, 2018) and previous surveys in the same region (Bickford et al, 2018, 2020), showing weak PSF magnitude and negligible evidence of differential microbial community cultivation (no differences in bacterial, fungal, or oomycete communities in roots or rhizosphere) in field conditions. This agreement gives us confidence that PSFs are not the primary driver of non‐native Phragmites ’ advantage over native Phragmites , at least in North American Great Lakes populations.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our experimental results are also in agreement with the only other PSF experiment on Phragmites (Allen et al, 2018) and previous surveys in the same region (Bickford et al, 2018, 2020), showing weak PSF magnitude and negligible evidence of differential microbial community cultivation (no differences in bacterial, fungal, or oomycete communities in roots or rhizosphere) in field conditions. This agreement gives us confidence that PSFs are not the primary driver of non‐native Phragmites ’ advantage over native Phragmites , at least in North American Great Lakes populations.…”
Section: Discussionsupporting
confidence: 92%
“…See Appendix S1: Table S3 for specific primer sequences and PCR conditions. We did not identify oomycete communities in soils due to the lack of community differences and low phylogenetic resolution obtained from small amplicons of oomycetes, which we have previously documented in these soils (Bickford et al, 2020). All PCR reactions were performed in triplicate using Phusion High Fidelity DNA Polymerase and master mix (New England BioLabs, Massachusetts, USA).…”
Section: Soil Molecular Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of studies are investigating the below‐ground microbial impacts of Phragmites . Consistent with our finding that Phragmites had weak effects on microbes in freshwater marshes, work from freshwater marshes on the Midwest and East Coast has shown minimal effects of haplotype M on bacteria, fungi and oomycetes (Bickford et al., 2020) and effects of haplotype M on oomycete pathogen composition but mixed effects on oomycete richness (Nelson & Karp, 2013). Another study in freshwater to low salinity marshes on the East Coast showed that haplotype M altered composition of soil archaea, but not bacteria (Yarwood et al., 2016).…”
Section: Discussionsupporting
confidence: 89%
“…The inference deduced from that correspondence analysis showed that both N-NO 3 and sulfate were the best predictors of the sample's metagenome functional categories by contributing 45.5% and 46.4% variations, respectively (Table 3 and Figure 5). It has been confirmed that environmental factors, most particularly those related to chemical properties, drive soil microbiota diversity and structure [33,34]. It is also reported that the indirect influence of pedological soil properties on soil microbiome metabolic activities is unquantifiable [35].…”
Section: Discussionmentioning
confidence: 90%